Jihad & Co.: black markets and Islamist power - Ahmad, Aisha (Oxford University Press, 2017)
The rise of militant jihadist groups is one of the greatest international security crises in the world today. In civil wars across the modern Muslim world, Islamist groups have emerged out of the ashes, surged dramatically to power, and routed their rivals on the battlefield. From North Africa to the Middle East to South Asia, these jihadist groups have seized large swaths of territory and consolidated political control over disparate ethnic and tribal communities. Out of the most broken and ungovernable places on earth, they have built radical new jihadist proto-states out of enduring anarchy. Why have these ideologically-inspired Islamists been able to build state-like polities out of enduring civil war stalemate, while so many other powerful armed groups have failed to gain similar traction? What makes jihadists win? In Jihad & Co., Aisha Ahmad argues that there are hard economic reasons behind Islamist success. By tracking the financial origins of jihadists in Afghanistan, Somalia, Pakistan, Mali, and Iraq she uncovers the secret role an important but often-overlooked class plays in bringing Islamist groups to power: the local business community. To uncover the hidden nexus between business and Islamist interests in civil war, Ahmad journeys into war-torn bazaars to meet with these jihadists and the smugglers who financed their rise to power. From the arms markets in the Pakistani border region to the street markets of Mogadishu, their stories reveal a powerful economic logic behind the rise of Islamist power in civil wars. Behind the fiery rhetoric and impassioned ideological claims is the cold hard cash of the local war economy. By bringing the reader from the mosque to the market, Ahmad explains exactly why business, far more than religion, explains the rise of militant Islamist power across the modern Muslim world.